Compression Fractures and Partial Phenotype Rescue With a Low Phosphorus Diet in the Chihuahua Zebrafish Osteogenesis Imperfecta Model - Cotti, Silvia; Huysseune, Ann; Larionova, Daria; Koppe, Wolfgang; Forlino, Antonella; Witten, Paul Eckhard (Frontiers in Endocrinology, 2022)
Osteogenesis imperfecta (OI) is a group of heritable disorders affecting bone and other connective tissues. Dominant OI forms are mainly caused by mutations in collagen type I. Patients suffer from skeletal deformities, fractures of long bones and vertebral compression fractures from early childhood onward. Altered collagen structure and excess mineralisation are the main causes for the bone phenotype. The Chihuahua (Chi/+) zebrafish has become an important model for OI. Given that reduced dietary phosphorus (P) intake reduces the bone mineral content and promotes bone matrix formation in teleosts, including zebrafish, we tested whether a low dietary P (LP) intake mitigates the OI phenotype in the Chi/+ model. To answer this question, we characterised the Chi/+ vertebral column phenotype at a morphological, cellular and subcellular level. We present the first description of vertebral compression fractures in Chi/+ and assess the effects of LP diet on the Chi/+ phenotype (Chi/+LP). Compared to untreated Chi/+, two months of LP dietary treatment decreases vertebral deformities in the abdominal region and reduces shape variation of caudal vertebral bodies to a condition more similar to wild type (WT). At the histological level, the osteoid layer, covering the bone at the vertebral body endplates in WT zebrafish, is absent in Chi/+, but it is partially restored with the LP diet. Whole mount stained specimens and histological sections show various stages of vertebral compression fractures in Chi/+ and Chi/+LP animals. Both Chi/+ and Chi/+LP show abundant osteoclast activity compared to WT. Finally, the ultrastructure analysis of WT, Chi/+ and Chi/+LP shows Chi/+ and Chi/+LP osteoblasts with enlarged endoplasmic reticulum cisternae and a high protein content, consistent with intracellular retention of mutated collagen. Nevertheless, the secreted collagen in Chi/+LP appears better organised concerning fibre periodicity compared to Chi/+. Our findings suggest that a reduced mineral content of Chi/+ bone could explain the lower frequency of vertebral column deformities and the restored shape of the vertebral bodies in Chi/+LP animals. This, together with the improved quality of the bone extracellular matrix, suggests that two months of reduced dietary P intake can alleviate the severe bone phenotype in Chi/+ zebrafish.